Determining the Amount of Earthquake Displacement Using Differential Synthetic Aperture Radar Interferometry (D-InSAR) and Satellite Images of Sentinel-1 A: A Case Study of Sarpol-e Zahab City - Jacob Cherian (Advances in Engineering and Intelligence Systems)
One of the effects of an earthquake is the creation of displacement on the land surface. It’s important to determine displacement due to natural disasters such as earthquakes. So, it’s essential to identify height changes occurring on Earth due to these movements. Detecting these changes in the extent of field operations requires a lot of time and money; hence, satellite technology can be used to eliminate the limitations of field operations. This study aimed to determine the trend and rate of land surface changes in the Sarpol-e Zahab earthquake using Sentinel-1 A and D-InSAR methods. To  this end, two radar images of SAR from the Sentinel-1 A satellite were prepared before and during the earthquake. Then, these two images were registered based on a prepared radar file to produce the interferogram of the study area. After removing the topography phase, the removal of existing noise was done by the interferogram generated from the Goldstein filter. Then, to determine the real phase difference, the produced phases were corrected. Before changing phase to displacement, to improve the processing results, the refining phase and applying multiple corrections and the absolute generated phase were changed to displacement. The displacement map of Sarpol-e Zahab city resulted from an earthquake of 7.3 magnitudes, showing displacement between -1.6 and 68 centimeters. Also, the results of this study showed that maximum displacement occurred in the north and northwest of the city, namely the villages of Dasht-e Zahab, Sarpol suburb, and Posht-tang, because of the adjacency of the earthquake center. Given the advantages of using remote sensing data, such as the ability to check the displacement between any desired point with the proper precision on the interferogram and the extensive coverage of SAR images, it’s suggested to use radar data such as Sentinel-1 to investigate displacement of the land surface.